The C-terminal priming domain is strongly associated with the main body of bacteriophage φ6 RNA-dependent RNA polymerase - Sarin, L; Wright, S; Chen, Q; Degerth, L; Stuart, D; Grimes, J; Bamford, D; Poranen, M (2012)
Double-stranded RNA viruses encode a single protein species containing RNA-dependent RNA polymerase (RdRP) motifs. This protein is responsible for RNA transcription and replication. The architecture of viral RdRPs resembles that of a cupped right hand with fingers, palm and thumb domains. Those using de novo initiation have a flexible structural elaboration that constitutes the priming platform. Here we investigate the properties of the C-terminal priming domain of bacteriophage φ{symbol}6 to get insights into the role of an extended loop connecting this domain to the main body of the polymerase. Proteolyzed φ{symbol}6 RdRP that possesses a nick in the hinge region of this loop was better suited for de novo initiation. The clipped C-terminus remained associated with the main body of the polymerase via the anchor helix. The structurally flexible hinge region appeared to be involved in the control of priming platform movement. Moreover, we detected abortive initiation products for a bacteriophage RdRP. © 2012 Elsevier Inc.